2020
DOI: 10.3390/nu12051443
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Family-Based Lifestyle Education Program on Dietary Habits, Hepatic Fat and Adiposity Markers in 8–12-Year-Old Children with Overweight/Obesity

Abstract: Healthy lifestyle education programs are recommended for obesity prevention and treatment. However, there is no previous information on the effects of these programs on the reduction of hepatic fat percentage. The aims were (i) to examine the effectiveness of a 22-week family-based lifestyle education program on dietary habits, and (ii) to explore the associations of changes in dietary intake with percent hepatic fat reduction and adiposity in children with overweight/obesity. A total of 81 children with overw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Moreover, these findings were not associated only with dietary but also with obesity, blood high level of low density lipoprotein -cholesterol (LDL -Cholesterol) and high blood pressure. It is already well known that metabolic syndrome and cardiovascular risk later in life is strongly connected with health status in childhood, from early ages (overweight or obesity, hypertension, glucose tolerance impairment, level of serum uric acid, dyslipidemia) [12]. The more risk factors involved, the greater atherosclerotic plaques extension [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these findings were not associated only with dietary but also with obesity, blood high level of low density lipoprotein -cholesterol (LDL -Cholesterol) and high blood pressure. It is already well known that metabolic syndrome and cardiovascular risk later in life is strongly connected with health status in childhood, from early ages (overweight or obesity, hypertension, glucose tolerance impairment, level of serum uric acid, dyslipidemia) [12]. The more risk factors involved, the greater atherosclerotic plaques extension [13].…”
Section: Resultsmentioning
confidence: 99%
“…Snacks with high energy intake delayed the request for the next meal with less than an hour and did not reduce the energy consumed at the subsequent meal [32][33][34]. Positive results of some programs dedicated to improving eating habits in children had demonstrated that compliance on regular time table can change not only the alimentary habits but also can improve the quality of the diet, with higher energy intake at breakfast compared with afternoon [12].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have investigated MD and the development of non-communicable disease during childhood and adolescence. In spite of the particular attention to allergic-respiratory diseases and obesity [ 33 , 34 , 36 , 65 ], there are few reports regarding the correlation between MD and endocrinological, neuropsychological, gastrointestinal diseases, and more generally, with various early-onset autoimmune disorders [ 38 ]. Furthermore, although the link between obesity and MD are largely investigated, evidence is scarce regarding the association between MD and maintaining a correct body weight in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, despite adequate consumption of fruits and vegetables, preschool children are often exposed to sugary drinks, snacks, and an excessive intake of proteins and sodium [ 6 ]. A study performed on 619 Spanish children highlighted that a higher adherence rate to MD and higher cardiopulmonary fitness (measured with 20 m shuttle run test) are associated with lower waist circumference, an anthropometric parameter widely associated to an increased risk of cardiovascular diseases [ 34 ]. It is noteworthy how MD has a protective role against wheezing [ 35 ] and acute rhinosinusitis [ 36 ], two very frequent causes of pediatrician consultation in preschool age.…”
Section: MD In Preschool Agementioning
confidence: 99%
“…Primary prevention may involve mass media, social communication, and healthcare systems to support parents to a more empathic and less intrusive parenting attitude towards their children since early infancy (Atzil, Hendler, & Feldman, 2011). Secondary and tertiary prevention strategies need to implement nutritional assistance of children with obesity and their families with psychoeducational and psychotherapeutic approaches (Arenaza, Medrano, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%